College Students’ Uses of and Perceptions Towards YouTube as an Information Resource to Support University Courses - Abdullah Almobarraz (Progress in Machines and Systems, 2015)
Using YouTube in the education domain offers a wealth of opportunities for learning, sharing, and collaborating over the developing number of education-based networks. To examine the use of YouTube as a platform of learning along with the other resource materials available to students, this study explores the perceptions, attitudes, and experiences of undergraduate students related to the use of YouTube as an information resource to support their learning. The use of YouTube by professors for course activities is also examined.